Challenges to Higher Education in Canada and Australia - Charles M. Beach; Frank Milne (Queen's University, Department of Economics, 2018)
This paper provides an overview of the higher education sector in Canada, so it can serve as a comparison to that in Australia. It seeks to identify stresses and challenges to this sector in Canada. The study also seeks to offer possible lessons for the direction of higher education policy in Australia and to raise concerns for the direction in Canada. The focus of the study is on the period since 2000 when consistent data for Canada largely became available. In 2005, the Rae Report – the last major overall review of higher education in Canada – was published followed by three volumes of evaluative studies of the state of higher education in Canada (Beach, Boadway and McInnis, 2005; Beach, 2005; and Iacobucci and Tuohy, 2005). So earlier and detailed commentaries are readily available from these sources. The present paper includes discussion of both universities as well as colleges that jointly make up the higher education sector in Canada. The perspective of the discussion is largely economic and heavily based on comparative statistics and the incentives they reveal. The paper proceeds as follows. The next section points out the major distinguishing features of the Canadian higher education system. Section 3 identifies a number of challenges and stresses the higher education sector has been facing in Canada. Then Section 4 examines some background influences on the higher education sector in both Australia and Canada. Section 5 then raises concerns about the growing role of metrics in higher education and the incentive issues they raise. And Section 6 concludes with some lessons to be considered in both countries' tertiary education sectors.
Keywords: A22; A23; H52; I22; I23; 330; Higher Education; Postsecondary Education; Australia-Canada Comparison